Laboratory studies of wind action on water standing in a channel - Hidy, George M., author; Plate, Erich J., author; Colorado State University, publisher (Colorado State University. Libraries, 1965)
The processes of wave and current development resulting from wind action on initially standing water have been investigated in a wind-water tunnel. The mean air flow over wavy water was examined along with the variation of speed. Measurements of phase speed and length of significant waves, the standard deviation of the water surface, the average surface drift, the auto-correlation of surface displacement and the frequency spectra are reported. The experimental results indicate that (a) the air motion in the channel follows a three-dimensional pattern characteristic of wind tunnels of rectangular cross-section; (b) wind waves generated in the channel travel downstream at approximately the same speed as gravity waves of small amplitude, provided the effect of the drift current is taken into account; (c) the average drag coefficients for the action of the wind on the water surface increase with increasing wind speed, and these data are reasonably consistent with results of previous investigators; (d) the autocorrelations and frequency spectra indicate that the wind waves in the channel consist of nearly regular primary waves on which are superimposed smaller ripples; (e) energy in the high frequency range in the spectra tends to approach an equilibrium distribution while the lower frequency components continue to grow with increasing fetch; and (f) a similarity shape for the frequency spectra develops. The experiments in this study were not intended to model the processes of interaction between the ocean and the atmosphere. Neverless the small waves generated in the channel appear to be at least qualitatively related to the development of waves on much larger bodies of water.
CER65GMH-EJP22.
Keywords: Winds; Water currents